Polyurethane foam
A polyurethane foam with low hardness and high impact modulus is achieved by incorporating a hydroxycarboxylic acid salt into the polymer chain, addressing the excessive hardness issue in conventional foams and enhancing rebound modulus without costly additives.
Patent Information
- Application Number
- JP2023100302
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
Conventional high resilience polyurethane foams face issues with excessive hardness due to the formation of urea bonds, leading to increased costs when using hardness reducing agents, and there is a need for a polyurethane foam with low hardness, high impact modulus, and low density without relying on expensive materials.
The polyurethane foam is produced by reacting a raw material mixture containing a polyol component, a blowing agent, a polyisocyanate component, and a hydroxycarboxylic acid salt, which incorporates the hydroxycarboxylate into the polymer chain to form part of the hard segment, reducing hardness and improving rebound modulus.
The foam achieves low hardness and maintains low density with improved rebound modulus, eliminating the need for expensive additives and maintaining high productivity through a one-shot method.
Smart Images

Figure 2025000443000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyurethane foam, and more particularly to a low-hardness polyurethane foam produced from a raw material mixture containing a hydroxycarboxylate salt. [Background technology]
[0002] Polyurethane refers to a polymeric compound having a urethane bond (-NH-C(O)O-). Polyurethane is obtained by reacting the hydroxyl group (-OH) of a polyol with the isocyanate group (-NCO) of a polyisocyanate. It is known that polyurethane exhibits a variety of properties by optimizing the type of polyol and / or polyisocyanate. For this reason, polyurethane is used in various automobile parts, synthetic leather, paints, adhesives, etc. Furthermore, polyurethane foam, which is made by foaming polyurethane, is used in insulation materials, cushioning materials, etc.
[0003] Polyurethane foams with interconnected cells exhibit viscoelasticity. Among them, polyurethane foams with enhanced elasticity are particularly called "high-resilience polyurethane foams." High-resilience polyurethane foams have a strong restoring force and are resistant to sagging, so they are used in apparel, sporting goods, toys, bedding, interior decoration, and more.
[0004] Various proposals have been made regarding such high-resilience polyurethane foams. For example, Patent Document 1 states: (a) Polyol A (functional group number = 3, hydroxyl value = 60.4 mg KOH / g) obtained by addition polymerization of EO and PO to glycerin: 100 parts by mass, (b) foam stabilizer (L-5740S): 1.5 parts by mass, (c) Catalyst (THN): 0.3 parts by mass, (d) Catalyst (XDM): 0.5 parts by mass, (e) Foaming agent (water): 1.5 parts by mass, (f) flame retardant (CR-505): 10 parts by mass, (g) catalyst (stannous octoate): 0.1 parts by mass, and (h) Polyisocyanate (TDI-80): an amount equivalent to an isocyanate index of 100 A flexible urethane foam obtained by reacting and foaming a raw material mixture containing the above is disclosed.
[0005] The document states that by such a method, (A) Density is 27.3 kg / m 3 and (B) Hardness is 8.0kg / 314cm 2 and (C) Resilience is 44% It is described that a flexible urethane foam can be obtained.
[0006] In Patent Document 2, (a) ethylene oxide + propylene oxide copolymer polyether polyol (EO = 72 wt%, trifunctional, hydroxyl value = 52 mg KOH / g): 60 parts by mass, (b) propylene oxide polymer polyether polyol (trifunctional, hydroxyl value = 56 mg KOH / g): 30 parts by mass, (c) trifunctional low molecular weight polyol compound (hydroxyl value = 400 mg KOH / g): 10 parts by mass, (d) Catalyst (TEDA 33LV): 1.5 parts by mass, (e) foam stabilizer (SF2904): 3.0 parts by mass, (f) antioxidant (PEP11C): 2.0 parts by mass, (g) foaming agent (water): 1.2 parts by mass, and (h) Polyisocyanate (TDI-80): 25.21 parts by mass An open-cell flexible polyurethane foam is disclosed, which is obtained by reacting and foaming a raw material mixture containing the following:
[0007] The document states that by such a method, (A) Density is 68.2 kg / m 3 and (B) 25% hardness is 32.3N / 314cm 2 and (C) Resilience is 42% It is described that an open-cell flexible urethane foam can be obtained.
[0008] Patent Document 3 describes a polyurethane foam, but (a) Polystyrene-b-poly(4-vinylpyridine)-b-polystyrene (SPS triblock copolymer) was synthesized. (b) Dissolve the SPS triblock copolymer in a THF / methanol mixed solvent, and then add tetraethylene glycol (TEG) to the solution. (c) Pour the solution into a container and evaporate the solvent (THF, methanol). The resulting non-covalent elastomer is disclosed.
[0009] The same document states: (A) Such a method provides a soft elastomer that exhibits a low elastic modulus and high stretchability without being denatured by solvent evaporation; and (B) The reason why the obtained elastomer exhibits a low elastic modulus and high elasticity is that the pyridyl group of the P chain (poly(4-vinylpyridine) chain) in the SPS triblock copolymer and the terminal hydroxyl group of the TEG form a supramolecular bridge through hydrogen bonding, and the TEG functions as a solvent for the P chain. is stated.
[0010] Patent Document 1 describes that a soft polyurethane foam with low density, low hardness, and high resilience can be obtained by using a special polyoxyalkylene polyol. Patent Document 2 describes that a soft polyurethane foam with high density, high breathability, and high resilience can be obtained by using three types of polyols. However, the use of a special polyol or the use of multiple types of polyols causes a decrease in cost competitiveness.
[0011] In addition, polyurethane (a) a soft domain comprising a soft segment derived from a long-chain polyol; (b) Hard domains formed by aggregation of hard segments derived from polyisocyanate It has a microphase-separated structure in which the phases are separated. The soft segment gives polyurethane flexibility, while the hard segment gives polyurethane toughness. Therefore, by controlling the microphase separation structure of such polyurethane foam, it is possible to control the hardness and impact resilience.
[0012] In polyurethane foam, the hard segments contain urethane bonds or urea bonds. Since urethane bonds and urea bonds have strong cohesive forces, adjacent hard segments are cohesive through hydrogen bonds to form hard domains. Furthermore, when the amount of water added is relatively large, urea bonds are more likely to form than urethane bonds. Since urea bonds have a stronger cohesive force than urethane bonds, when the amount of water added is excessive, hard domains containing urea bonds may aggregate into spherical shapes (so-called "urea balls"), which is a problem that conventional high-resilience polyurethane foams are prone to excessive hardness increase.
[0013] On the other hand, in order to solve this problem, it is possible to add a hardness reducing agent (e.g., zeolite 213) to the raw material. However, since the hardness reducing agent is expensive, the use of the hardness reducing agent reduces cost competitiveness. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] Patent No. 2990215 (Japanese Unexamined Patent Publication No. 06-025373) [Patent Document 2] Patent No. 5368667 (JP 2006-335945 A) [Patent Document 3] Patent Publication No. 6516388 (International Publication No. 2016 / 181834) Summary of the Invention [Problem to be solved by the invention]
[0015] An object of the present invention is to provide a novel polyurethane foam exhibiting low hardness without using expensive raw materials. Another object of the present invention is to provide a novel polyurethane foam which exhibits high impact resilience and low density in addition to low hardness. [Means for solving the problem]
[0016] In order to solve the above problems, the polyurethane foam of the present invention is obtained by reacting and foaming a raw material mixture containing a polyol component, a blowing agent, a polyisocyanate component, and a hydroxycarboxylate salt. Effect of the Invention
[0017] In the production of polyurethane foam, adding an appropriate amount of hydroxycarboxylate to the raw material mixture can reduce the hardness of the polyurethane foam while maintaining a low density. In addition, the reduction in hardness usually improves the rebound resilience of the polyurethane foam. This is because (a) The hydroxyl group of the hydroxycarboxylate reacts with the isocyanate group of the polyisocyanate, whereby the hydroxycarboxylate is incorporated into the polymer chain and constitutes a part of the hard segment; and (b) Ionic bond moiety (-COO - M + ) relaxes the hydrogen bonds between the hard segments. It is thought that. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An embodiment of the present invention will be described in detail below. [1. Polyurethane foam] The polyurethane foam according to the present invention is A polyol component; A foaming agent; A polyisocyanate component; Hydroxycarboxylate and The foaming agent is obtained by reacting and foaming a raw material mixture containing the above. The raw material mixture usually further contains a foam stabilizer and a catalyst. The raw material mixture may further contain other additives as necessary.
[0019] [1.1. Ingredients] [1.1.1. Polyol component] [A. Materials] The raw material mixture contains a polyol component. The polyol component may contain only one type of polyol, or may contain two or more types of polyols. In order to reduce the cost of the polyurethane foam, it is preferable that the polyol component contains only one type of polyol.
[0020] The polyol is (a) a polyether polyol obtained by addition polymerization of an alkylene oxide to an initiator; (b) a polyester polyol obtained by dehydration condensation of a carboxylic acid and a polyhydric alcohol; (c) A polymer polyol in which polymer particles obtained by copolymerizing acrylonitrile or styrene are dispersed in a polyether polyol. Either of the above may be used. In order to obtain a polyurethane foam having a low hardness, the polyol is preferably a polyether polyol.
[0021] [B. Weight average molecular weight] The weight average molecular weight of the polyol component mainly affects the hardness and resilience of the polyurethane foam. If the weight average molecular weight of the polyol component is too small, the hardness of the polyurethane foam may be excessively high. This may also result in the resilience of the polyurethane foam being excessively low. Therefore, the weight average molecular weight of the polyol component is preferably 560 or more. The weight average molecular weight is more preferably 700 or more, 800 or more, 900 or more, or 1000 or more. On the other hand, if the weight average molecular weight of the polyol component is too large, it will lead to high costs. Therefore, the weight average molecular weight of the polyol component is preferably 13600 or less. The weight average molecular weight is more preferably 10000 or less, 9000 or less, 8000 or less, or 7000 or less.
[0022] [C. Average number of functional groups] The average functionality of the polyol component mainly affects the hardness and impact resilience of the polyurethane foam. The higher the average functionality of the polyol component, the higher the hardness. To achieve such an effect, the average functionality of the polyol component is preferably 2.0 or more. The average functionality is more preferably 2.3 or more, 2.5 or more, or 2.7 or more. On the other hand, if the average functionality of the polyol component is excessive, the hardness of the polyurethane foam may be excessively high. This may also result in the rebound resilience of the polyurethane foam being excessively low. Therefore, the average functionality of the polyol component is preferably 4.0 or less. The average functionality is more preferably 3.8 or less, 3.6 or less, or 3.4 or less.
[0023] [D. Average hydroxyl value] The average hydroxyl value of the polyol component mainly affects the hardness and resilience of the polyurethane foam. If the average hydroxyl value of the polyol component is too small, it will lead to high costs. Therefore, the average hydroxyl value of the polyol component is preferably 16.5 mgKOH / g or more. The average hydroxyl value is more preferably 20.0 mgKOH / g or more, 30.0 mgKOH / g or more, or 33.0 mgKOH / g or more. On the other hand, if the average hydroxyl value of the polyol component is too large, the hardness of the polyurethane foam may become excessively high. This may also result in the polyurethane foam having an excessively low resilience modulus. Therefore, the average hydroxyl value of the polyol component is preferably 400.7 mgKOH / g or less. The average hydroxyl value is more preferably 300 mgKOH / g or less, 200 mgKOH / g or less, or 100 mgKOH / g or less.
[0024] [E. EO content] The "EO content" refers to the ratio of the mass of ethylene oxide (EO) units to the total mass of alkylene oxide units contained in the polyether polyol. When the polyether polyol contains alkylene oxide units other than EO units, the alkylene oxide units other than EO units are not particularly limited, but are preferably propylene oxide (PO) units.
[0025] When a polyether polyol is used as the polyol, it is preferable to select an optimal value for the EO content of the polyether polyol depending on the purpose. In general, if the EO content of the polyether polyol is too high, the hydrophilicity of the polyurethane foam becomes excessively high, and the moist heat compression set may deteriorate. Alternatively, if the hydrophilicity of the polyurethane foam becomes excessively high, the foam may easily swell, and the moist heat aging property may deteriorate significantly. Therefore, the EO content is preferably 15 mass% or less. The EO content is more preferably 10 mass% or less, or 5 mass% or less.
[0026] [1.1.2. Foaming agent] The raw material mixture contains a foaming agent. The "foaming agent" refers to an additive for generating bubbles in the raw material mixture during the process of resinification of the liquid raw material mixture. In the present invention, the blowing agent is (a) A physical blowing agent that generates gas upon pressure reduction or heating; or (b) Chemical foaming agents that generate gas by thermal decomposition or chemical reaction Either of the above may be used.
[0027] Examples of physical foaming agents include: (a-1) Hydrocarbons such as cyclopentane, isopentane, and normal pentane, (a-2) Halogen-based compounds such as methylene chloride, trichlorofluoromethane, dichlorodifluoromethane, nonafluorobutyl methyl ether, pentafluoroethyl methyl ether, and pentafluoroisopropyl methyl ether; etc.
[0028] Examples of chemical foaming agents include: (b-1) Water that reacts with isocyanate groups to generate CO2; (b-2) Azodicarbonamide that generates nitrogen, carbon monoxide, carbon dioxide, or ammonia gas upon thermal decomposition etc.
[0029] The raw material mixture may contain any one of these blowing agents, or may contain two or more of them. Among these, the foaming agent is preferably water. When water is used as the foaming agent, CO2 gas generated by the reaction of water with isocyanate groups promotes foaming. In addition, the reaction heat between water and isocyanate groups promotes the curing of the resin.
[0030] [1.1.3. Polyisocyanate component] The raw material mixture contains a polyisocyanate component. The polyisocyanate component may contain one type of polyisocyanate, or may contain two or more types of polyisocyanates. Furthermore, the number of functional groups of the polyisocyanate is not particularly limited, and the optimal number of functional groups can be selected depending on the purpose.
[0031] The polyisocyanate is (a) Aromatic isocyanate compounds, aliphatic isocyanate compounds, or alicyclic isocyanate compounds, (b) Modified products of the above compounds etc.
[0032] Examples of aromatic isocyanate compounds include: Diphenylmethane diisocyanate (MDI), Crude diphenylmethane diisocyanate, tolylene diisocyanate (TDI), Naphthalene diisocyanate (NDI), p-Phenylene diisocyanate (PPDI), Xylene diisocyanate (XDI), Tetramethylxylene diisocyanate (TMXDI), Tolidin diisocyanate (TODI) and the like.
[0033] Examples of the aliphatic isocyanate compound include: Hexamethylene diisocyanate (HDI), Lysine diisocyanate (LDI), Examples include lysine triisocyanate (LTI).
[0034] Examples of the alicyclic isocyanate compound include: Isophorone diisocyanate (IPDI), Cyclohexyl diisocyanate (CHDI), hydrogenated XDI (H6XDI), Hydrogenated MDI (H 12 MDI) etc.
[0035] Examples of modified isocyanate compounds include urethane-modified, dimer-, trimer-, carbodiimide-modified, allophanate-modified, biuret-modified, urea-modified, isocyanurate-modified, oxazolidone-modified, and isocyanate-terminated prepolymers of isocyanate compounds.
[0036] [1.1.4. Hydroxycarboxylates] The raw material mixture contains a hydroxycarboxylate. The term "hydroxycarboxylate" refers to a salt formed by reacting a hydroxycarboxylic acid with a base. The hydroxycarboxylic acid may have one hydroxyl group, or may have two or more hydroxyl groups. Similarly, the hydroxycarboxylic acid may have one carboxy group or may have two or more carboxy groups.
[0037] The raw material mixture may contain any one kind of hydroxycarboxylate, or may contain two or more kinds of hydroxycarboxylates. Adding a hydroxycarboxylate to the raw material mixture can reduce the hardness of the polyurethane foam. This is thought to be because the hydroxyl group of the hydroxycarboxylate reacts with the isocyanate group of the polyisocyanate, and the hydroxycarboxylate is incorporated into the polymer chain and forms part of the hard segment.
[0038] Examples of the cation contained in the hydroxycarboxylate include: (a) Ions of group 1 elements excluding hydrogen (Li, Na, K, Rb, Cs, Fr), (b) ions of group 2 elements (Be, Mg, Ca, Sr, Ba, Ra), (c) ions of metal elements or metalloid elements belonging to groups 3 to 16 (e.g., Mn, Fe, Co, Ni, Cu, Zn, etc.); (d) Ammonium ion, primary ammonium ion, secondary ammonium ion, tertiary ammonium ion, quaternary ammonium ion, etc.
[0039] Specific examples of hydroxycarboxylic acids include: (a) Aliphatic hydroxycarboxylic acids such as glycolic acid, lactic acid, tartronic acid, glyceric acid, hydroxybutyric acid, malic acid, tartaric acid, citramalic acid, citric acid, isocitric acid, leucic acid, mevalonic acid, pantoic acid, ricinoleic acid, ricinelaizic acid, cerebronic acid, quinic acid, shikimic acid, and hydroxylauric acid; (b) Aromatic hydroxycarboxylic acids, such as salicylic acid, hydroxy(methyl)benzoic acid, vanillic acid, syringic acid, pyrocatechuic acid, resorcylic acid, protocatechuic acid, gentisic acid, orselliic acid, gallic acid, mandelic acid, benzilic acid, atrolactic acid, mellitic acid, phloretic acid, coumaric acid, umbellic acid, caffeic acid, ferulic acid, and sinapic acid; (c) Hydroxycarboxylic acids in which part of the main chain or skeleton is substituted with oxygen or sulfur, such as lauryl glycol carboxylic acid; etc.
[0040] Among these, hydroxycarboxylates are (a) sodium potassium tartrate tetrahydrate, or (b) sodium lauryl glycol carboxylate, is preferred. Sodium potassium tartrate tetrahydrate has a significant effect of decreasing the hardness of polyurethane foam, increasing the rebound resilience, and decreasing the dry heat compression set. On the other hand, sodium lauryl glycol carboxylate has a large effect of decreasing the hardness of the polyurethane foam, increasing the impact resilience, and increasing the elongation.
[0041] Catalysts The raw material mixture usually contains a catalyst. The term "catalyst" refers to a catalyst that has a large effect of promoting the resinification reaction, a catalyst that has a large effect of promoting the foaming reaction (the reaction between isocyanate groups and water), or a catalyst that has an effect of promoting both the resinification reaction and the foaming reaction. In the present invention, the type of catalyst is not particularly limited, and an optimal catalyst can be selected depending on the purpose.
[0042] Examples of catalysts include amine catalysts and metal catalysts. Amine catalysts are catalysts that have the effect of promoting both the resinification reaction and the foaming reaction. Metal catalysts are catalysts that have a strong effect of promoting the resinification reaction. The raw material mixture may contain any one of these catalysts, or may contain two or more of them.
[0043] Examples of the amine catalyst include: N,N-dimethylcyclohexylamine, N,N-dimethylbenzylamine, N,N-Dimethylaminoethanol, N,N-Dimethylaminohexanol, N,N',N'-trimethylaminoethylpiperazine, triethylenediamine etc.
[0044] Examples of metal catalysts include: (a) Tin catalysts such as stannous octoate and dibutyltin dilaurate, (b) mercury catalysts, such as phenylmercury propionate; (c) Lead catalysts such as lead octenate etc.
[0045] [1.1.6. Foam stabilizer] The raw material mixture usually contains a foam stabilizer, which is an additive that has the effect of making the size and distribution of bubbles uniform. Adding a foam stabilizer to the raw material mixture makes it possible to obtain polyurethane foam with uniform bubble size and distribution. Examples of foam stabilizers include silicone-based foam stabilizers, fluorine-containing compound-based foam stabilizers, and known surfactants.
[0046] [1.2. Content] [1.2.1. Hydroxycarboxylate content] The "content of hydroxycarboxylate" refers to the mass of the hydroxycarboxylate when the mass of the polyol component is taken as 100. It is preferable to select an optimum content of the hydroxycarboxylate depending on the type of the hydroxycarboxylate.
[0047] [A. Sodium potassium tartrate tetrahydrate content] For example, when sodium potassium tartrate tetrahydrate is used as the hydroxycarboxylate, if the content of sodium potassium tartrate tetrahydrate is too small, the hardness of the polyurethane foam may become high. Therefore, the content of sodium potassium tartrate tetrahydrate is preferably 0.05 parts by mass or more. The content is more preferably 0.07 parts by mass or more, or 0.10 parts by mass or more.
[0048] On the other hand, if the content of sodium potassium tartrate tetrahydrate is excessive, the bubbles in the polyurethane foam tend to become closed bubbles. As a result, the foam may shrink during the cooling process after the reaction. This is believed to be because the pH of the raw material mixture becomes excessively high due to the sodium contained in sodium potassium tartrate tetrahydrate, which excessively promotes the resinification reaction of the raw material mixture. Therefore, the content of sodium potassium tartrate tetrahydrate is preferably 0.80 parts by mass or less. The content is more preferably 0.75 parts by mass or less, or 0.70 parts by mass or less.
[0049] [B. Sodium lauryl glycol carboxylate content] When sodium lauryl glycol carboxylate is used as the hydroxycarboxylate, if the content of sodium lauryl glycol carboxylate is too small, the hardness of the polyurethane foam may become high. Therefore, the content of sodium lauryl glycol carboxylate is preferably 0.05 parts by mass or more. The content is more preferably 0.07 parts by mass or more, or 0.10 parts by mass or more.
[0050] On the other hand, if the content of sodium lauryl glycol carboxylate is excessive, the bubbles in the polyurethane foam tend to become closed bubbles, and the foam may shrink during the cooling process after the reaction. This is believed to be due to the sodium contained in sodium lauryl glycol carboxylate excessively promoting the resinification reaction. Furthermore, if the content of sodium lauryl glycol carboxylate is excessive, the dry heat compression set of the polyurethane foam may increase. Therefore, the content of sodium lauryl glycol carboxylate is preferably 1.20 parts by mass or less. The content is more preferably 1.15 parts by mass or less, or 1.10 parts by mass or less.
[0051] [1.2.2. Foaming agent content] The "content of the blowing agent" refers to the mass of the blowing agent when the mass of the polyol component is taken as 100. It is preferable to select an optimum content of the foaming agent depending on the type of the foaming agent.
[0052] For example, when the blowing agent is water, if the water content is too low, the density of the polyurethane foam may become excessively high. Therefore, the water content is preferably 1.0 part by mass or more. The content is more preferably 1.5 parts by mass or more, or 2.0 parts by mass or more. On the other hand, if the water content is excessive, the heat generation temperature due to the reaction (foaming reaction and resinification reaction) becomes excessively high, and scorching (burning, scorching) may occur in the polyurethane foam. Therefore, the water content is preferably 5.0 parts by mass or less. The content is more preferably 4.5 parts by mass or less, or 4.0 parts by mass or less.
[0053] [1.2.3. Content of polyisocyanate component] "Isocyanate index" refers to the ratio of the equivalent weight of isocyanate groups of the polyisocyanate in the raw material mixture to the equivalent weight of active hydrogen groups in the raw material mixture, multiplied by 100.
[0054] If the isocyanate index is too small, the hardness of the polyurethane foam may be excessively reduced. Also, the crosslink density may be excessively reduced, and foam may not be formed. Therefore, the isocyanate index is preferably 80 or more. The isocyanate index is more preferably 85 or more, 90 or more, 95 or more, or 100 or more. On the other hand, if the isocyanate index is too large, the polyurethane foam may become excessively hard. Therefore, the isocyanate index is preferably 200 or less. The isocyanate index is more preferably 180 or less, 160 or less, 140 or less, or 120 or less.
[0055] [1.2.4. Catalyst content] The "content of catalyst" refers to the mass of the catalyst when the mass of the polyol component is taken as 100. When two or more types of catalysts are used, the "mass of catalyst" refers to the total mass of the two or more types of catalysts.
[0056] In general, the higher the catalyst content, the shorter the reaction time. To obtain such an effect, the catalyst content is preferably 0.01 parts by mass or more. More preferably, the content is 0.05 parts by mass or more, 0.10 parts by mass or more, or 0.20 parts by mass or more. On the other hand, if the catalyst content is excessive, the polyurethane foam may become too hard. Therefore, the catalyst content is preferably 1.0 part by mass or less. The content is more preferably 0.8 parts by mass or less, 0.6 parts by mass or less, or 0.4 parts by mass or less.
[0057] [1.2.5. Content of foam stabilizer] The "content of foam stabilizer" refers to the mass of the foam stabilizer when the mass of the polyol component is taken as 100.
[0058] If the content of the foam stabilizer is too low, it may be difficult to form a foam. Therefore, the content of the foam stabilizer is preferably 0.1 parts by mass or more. The content is more preferably 0.3 parts by mass or more, or 0.5 parts by mass or more. On the other hand, if the content of the foam stabilizer is excessive, closed cells may be formed, impairing breathability, or the foam may shrink after the reaction. Therefore, the content of the foam stabilizer is preferably 3.0 parts by mass or less. The content is more preferably 2.5 parts by mass or less, 2.0 parts by mass or less, 1.5 parts by mass or less, or 1.0 part by mass or less.
[0059] [1.3. Reaction] The polyisocyanate component (liquid B) is added to and mixed with the raw material mixture (liquid A) containing the polyol component and other additives, and the raw material mixture is maintained at a predetermined temperature. This causes a foaming reaction and a resinification reaction to occur, resulting in the production of the polyurethane foam according to the present invention.
[0060] In producing the polyurethane foam according to the present invention, either slab foaming or mold foaming may be used. "Slab foaming" refers to a method in which a raw material mixture for producing polyurethane foam is discharged onto a belt conveyor and foamed at atmospheric pressure and room temperature. "Mold foaming" refers to a method in which a mixture of raw materials for producing polyurethane foam is injected into the cavity of a mold and foamed within the cavity.
[0061] [1.4. Characteristics] 1.4.1. 25% ILD Hardness "25% ILD hardness" refers to a value measured in accordance with JIS K 6400-2:2012.
[0062] The polyurethane foam according to the present invention exhibits a lower hardness than polyurethane foams containing no hydroxycarboxylate salt. When the production conditions of the polyurethane foam according to the present invention are optimized, the 25% ILD hardness becomes 150N or less. When the production conditions are further optimized, the 25% ILD hardness becomes 140N or less, 130N or less, 120N or less, or 110N or less. By optimizing the manufacturing conditions, polyurethane foams with a minimum 25% ILD hardness of 50N, 60N, 70N, or even 80N can be manufactured.
[0063] [1.4.2. Rebound elasticity] "Rebound resilience" refers to a value measured in accordance with JIS K 6400-3:2011.
[0064] The polyurethane foam according to the present invention may exhibit a higher resilience than polyurethane foams containing no hydroxycarboxylate. When the production conditions of the polyurethane foam according to the present invention are optimized, the resilience is 30% or more. When the production conditions are further optimized, the resilience is 35% or more, 40% or more, or 45% or more. By optimizing the manufacturing conditions, it is possible to produce polyurethane foam with a maximum resilience of 55% or even 50%.
[0065] [1.4.3. Density] "Density" refers to a value measured in accordance with JIS K 7222:2005.
[0066] The density of the polyurethane foam mainly depends on the amount of the blowing agent. When the production conditions of the polyurethane foam according to the present invention are optimized, the density is 30 kg / m 3 If the manufacturing conditions are further optimized, the density will be 28 kg / m 3 Less than or equal to 26kg / m 3 The result is as follows. On the other hand, if the density is too low, the rigidity and / or the resilience may be excessively reduced. Therefore, the density is 16 kg / m 3 The above is preferred.
[0067] 1.4.4. Tensile strength "Tensile strength" refers to a value measured in accordance with JIS K 6400-5:2012.
[0068] The polyurethane foam according to the present invention has a lower hardness than polyurethane foam not containing a hydroxycarboxylate, but the decrease in tensile strength is small. When the production conditions of the polyurethane foam according to the present invention are optimized, the tensile strength becomes 70 kPa or more. When the production conditions are further optimized, the tensile strength becomes 75 kPa or more, or 80 kPa or more. By optimizing the manufacturing conditions, polyurethane foams with tensile strengths of up to 110 kPa, 105 kPa, or even 100 kPa can be produced.
[0069] 1.4.5. Elongation rate "Elongation" refers to a value measured in accordance with JIS K 6400-5:2012.
[0070] The polyurethane foam according to the present invention may exhibit a higher elongation percentage than polyurethane foams containing no hydroxycarboxylate. When the production conditions of the polyurethane foam according to the present invention are optimized, the elongation percentage can be 140% or more. When the production conditions are further optimized, the elongation percentage can be 145% or more, 150% or more, or 160% or more. By optimizing the manufacturing conditions, polyurethane foams with elongations of up to 230%, 225%, or even 220% can be produced.
[0071] [1.4.6. Tear strength] "Tear strength" refers to a value measured in accordance with JIS K 6400-5:2012.
[0072] The polyurethane foam according to the present invention has a lower hardness than polyurethane foam not containing a hydroxycarboxylate, but the decrease in tear strength is small. When the production conditions of the polyurethane foam according to the present invention are optimized, the tear strength becomes 4.0 N / cm or more. When the production conditions are further optimized, the tear strength becomes 4.2 N / cm or more, 4.5 N / cm or more, or 5.0 N / cm or more. By optimizing the manufacturing conditions, it is possible to produce polyurethane foams with tear strengths of up to 7.0 N / cm, 6.5 N / cm, or even 6.0 N / cm.
[0073] [1.4.7. Dry heat compression set] "Dry heat compression set" refers to a value measured in accordance with JIS K 6400-4:2004.
[0074] In the polyurethane foam of the present invention, optimizing the type and amount of hydroxycarboxylate salt can provide a polyurethane foam with a small dry heat compression set. In the polyurethane foam of the present invention, optimizing the manufacturing conditions can provide a dry heat compression set of 45% or less. Further optimizing the manufacturing conditions can provide a dry heat compression set of 40% or less, 30% or less, 10% or less, 5% or less, 4% or less, or 3.0% or less. By optimizing the manufacturing conditions, it is possible to produce polyurethane foam with a dry heat compression set of at least 1.0%.
[0075] [1.4.8. ASTM Ventilation] "ASTM Air Permeability" refers to values measured in accordance with ASTM D 3574.
[0076] The polyurethane foam according to the present invention has high breathability because it contains interconnected cells. When the manufacturing conditions are optimized, the ASTM air permeability is 0.5 L / min or more. When the manufacturing conditions are further optimized, the ASTM air permeability is 1.0 L / min or more, 5.0 L / min or more, 10.0 L / min or more, or 20.0 L / min or more. By optimizing the manufacturing conditions, polyurethane foams with ASTM air permeability of up to 160 L / min, 140 L / cm, 120 L / cm, or even 100 L / cm can be manufactured.
[0077] [1.5. Purpose] The polyurethane foam according to the present invention can be used in various applications requiring low density, low hardness, and high resilience. (a) Bra pads, (b) Automotive seat cushion components (e.g., various laminated products manufactured using the frame lamination (FL) method, rest pads, cover pads, etc.); (c) Bedding (mattresses, pillows), (d) Furniture cushioning It can be used in the following ways:
[0078] [2. Effect] Polyurethane has a microphase separation structure in which soft domains made of soft segments and hard domains made of hard segments are separated. The urethane bonds and urea bonds contained in the hard segments have strong cohesive forces, and adjacent hard segments form aggregates via hydrogen bonds. Therefore, conventional high-resilience polyurethane foams have the problem of being prone to high hardness.
[0079] In contrast, when a polyurethane foam is produced, if an appropriate amount of a hydroxycarboxylate is added to the raw material mixture, the hardness of the polyurethane foam can be reduced while maintaining a low density. Furthermore, the reduction in hardness usually leads to an improvement in the rebound resilience of the polyurethane foam. This is because (a) The hydroxyl group of the hydroxycarboxylate reacts with the isocyanate group of the polyisocyanate, whereby the hydroxycarboxylate is incorporated into the polymer chain and constitutes a part of the hard segment; and (b) Ionic bond moiety (-COO - M+ ) relaxes the hydrogen bonds between the hard segments. It is thought that.
[0080] The polyurethane foam according to the present invention can be produced by adding a small amount of an aqueous solution of a hydroxycarboxylate to a raw material mixture. In other words, there is no need to use a special polyol or an expensive hardness reducer to achieve low density, low hardness, and high resilience. In addition, the polyurethane foam according to the present invention can be foamed by a one-shot method, so there is little loss of raw materials and high productivity. EXAMPLES
[0081] (Examples 1 to 10, Comparative Example 1) [1. Sample preparation] [1.1. Raw materials] The following raw materials were used other than the hydroxycarboxylate. (1) Polyol: Polyether polyol (manufactured by Sanyo Chemical Industries, Ltd., "GP3050NS", OHV = 56.1, f = 3, molecular weight = 3000, EO content: about 8 mass%) (2) Foaming agent: Water (3) Catalyst 1: Amine catalyst (Kao Corporation, "No. 25", OHV=387) (4) Catalyst 2: Metal catalyst (manufactured by Johoku Chemical Industry Co., Ltd., "MRH-110") (5) Foam stabilizer: Silicone foam stabilizer (Momentive Corporation, "L-895") (6) Isocyanate: TDI (Mitsui Chemicals, Inc., "Cosmonate (registered trademark) T-80")
[0082] The following solutions containing hydroxycarboxylates (additives) were used: (1) Additive solution 1: Aqueous solution containing sodium lauryl glycol carboxylate (Additive 1) (manufactured by Sanyo Chemical Industries, Ltd., "Viewlite (registered trademark) SHAA", OHV = 199.0) (2) Additive solution 2: A solution obtained by dissolving sodium potassium tartrate tetrahydrate powder (Additive 2) (Kanto Chemical Co., Ltd., OHV = 397.8) in water
[0083] [1.2. Formation of foam] The above-mentioned raw materials were mixed in a predetermined ratio to obtain a raw material mixture. The raw material mixture was poured into a non-sealed foaming box (270 mm square, made of cardboard) with an open top, and the raw material mixture was allowed to foam freely in the foaming box. The foaming box containing the foam was then placed in an oven set at 70°C to harden the foam.
[0084] 2. Test Method [2.1. Density] The density of the foam was measured according to JIS K 7222:2005.
[0085] [2.2. 25% ILD hardness] The 25% ILD hardness of the foam was measured according to JIS K 6400-2:2012.
[0086] [2.3. Rebound elasticity] The foam's resilience was measured in accordance with JIS K 6400-3:2012.
[0087] 2.4. Tensile strength The tensile strength of the foam was measured according to JIS K 6400-5:2012.
[0088] [2.5. Growth rate] The elongation of the foam was measured according to JIS K 6400-5:2012.
[0089] [2.6. Tear strength] The tear strength of the foam was measured according to JIS K 6400-5:2012.
[0090] [2.7. Dry heat compression set] The dry heat compression set of the foam was measured according to JIS K 6400-4:2004.
[0091] [2.8. ASTM Ventilation] The ASTM air permeability of the foams was measured according to ASTM D 3574.
[0092] [3. Results] The results are shown in Table 1. The raw material composition of each sample is also shown in Table 1. Regarding the raw material composition, the numerical values other than the indexes each represent parts by mass.
[0093] Regarding the appearance of the form, "○" indicates that there is no foam shrinkage or foam lifting. "△" indicates that there was no foam shrinkage, but the foam rose slightly. An "x" indicates that the foam has shrunk. "Foam floating" refers to the phenomenon in which the reaction rate of the resinification reaction is so fast that the gas (CO2) generated during foaming cannot escape from the top of the foam, and the gas with nowhere to escape accumulates near the bottom of the foam.
[0094] Regarding hardness, "◯" indicates that the hardness is lower than that of Comparative Example 1.
[0095] Regarding the rebound elasticity, "○" indicates that the resilience is higher than that of Comparative Example 1. "X" indicates that the resilience modulus is equal to or lower than that of Comparative Example 1.
[0096] (1) When sodium lauryl glycol carboxylate was used as an additive (Examples 1 to 6), the hardness tended to decrease as the amount of additive increased. This is believed to be because the ionic bond portion introduced into the hard segment relaxes the hydrogen bond between the hard segments. (2) Examples 1 to 3 had improved resilience compared to Comparative Example 1. However, Examples 4 to 6 had lower resilience compared to Comparative Example 1. This is believed to be because Examples 4 to 6 had low breathability and slow recovery upon impact.
[0097] (3) Examples 1 to 6 had improved elongation compared to Comparative Example 1. It is believed that in Examples 1 to 6, ionic bond moieties were introduced into the hard segments, and adjacent ionic bond moieties aggregated together via ionic bonds. Therefore, it is believed that in Examples 1 to 6, even if an ionic bond moiety dissociates during the foam stretching process, it re-forms a bond with another nearby ionic bond moiety, resulting in improved elongation compared to Comparative Example 1. (4) In Examples 1 to 6, the more the amount of additive added, the larger the dry heat compression set and the lower the ASTM air permeability. This is thought to be because the more the amount of additive added, the more likely it is that closed cells are formed in the foam.
[0098] (5) When sodium potassium tartrate tetrahydrate was used as the additive (Examples 7 to 10), the hardness tended to decrease as the amount of additive increased. (6) In all of Examples 7 to 10, the resilience modulus was improved compared to Comparative Example 1. This is believed to be because sodium potassium tartrate tetrahydrate caused less decrease in breathability.
[0099] (7) In Examples 7 to 10, the elongation percentage was improved compared to Comparative Example 1, but the increment of the elongation percentage was decreased compared to Examples 1 to 6. Sodium lauryl glycol carboxylate has one OH group. On the other hand, sodium potassium tartrate tetrahydrate has two OH groups, and the positions of the OH groups in the structure are close to each other. Therefore, when sodium potassium tartrate tetrahydrate is used as an additive, if both of the two OH groups are bonded to an isocyanate group, it is considered that the degree of freedom of the polymer chain is reduced. As a result, it is considered that the increment of the elongation percentage in Examples 7 to 10 is decreased compared to Examples 1 to 6.
[0100] (8) In Examples 7 to 10, the dry heat compression set was smaller than that in Examples 1 to 6. This is because (a) Sodium potassium tartrate tetrahydrate has a greater steric hindrance than sodium lauryl glycol carboxylate, and (b) Sodium potassium tartrate tetrahydrate contains less sodium, which has a large effect of increasing the reaction rate of the resinification reaction, than sodium lauryl glycol carboxylate, and this suppresses the generation of closed cells. It is thought that.
[0101] [Table 1]
[0102] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0103] The polyurethane foam according to the present invention can be used for apparel products, sporting goods, toys, bedding, interior goods, and the like.
Claims
1. A polyurethane foam obtained by reacting and foaming a raw material mixture containing a polyol component, a blowing agent, a polyisocyanate component, and a hydroxycarboxylate.
2. 2. The polyurethane foam according to claim 1, having a 25% ILD hardness of 150 N or less.
3. 2. The polyurethane foam according to claim 1, having a rebound resilience of 30% or more and 55% or less.
4. Density is 16 kg / m 3 More than 30kg / m 3 2. The polyurethane foam according to claim 1, wherein:
Citation Information
Patent Citations
Rolling apparatus
JP1978068667A
Production of low-density and low-hardness soft urethane foam
JP1994025373A
Open-cell soft polyurethane foam and method for producing the same
JP2006335945A
Manufacturing method of soft urethane foam with low density and low hardness
JP2990215B2
Non-covalent soft elastomer and method for producing same
JP6516388B2